FOUR-DIMENSIONAL SPACE TIME STATIONARY AND AXIS-SYMETRIC EINSTEIN METRIC - (NIM: 20210007); Pembimbing : Dr. rer. nat. Bobby Eka Gunara, HASANUDDIN
In this paper, we construct Ernst equation from vacuum Einstein field equation for both zero and non-zero cosmological constant. In particular, we consider the case where the spacetime admits axissymmetric using Boyer-Lindquist coordinates. This is called Kerr-Einstein solution describing a spinning black hole. Finally, we give a short discussion about the dynamics of photons on Kerr-Einstein spacetimes.